Mediation of Agency Cost on Governance in Company Financial Performance - Ashari Sofyaun; Asrid Juniar; Rini Rahmawati (Budapest International Research and Critics University, 2022)
Financial performance in the perspective of governance with agency cost is the research objective. The study was conducted during the period 2013-2021 on state-owned companies on the Indonesian stock exchange with a purposive sampling method approach. Managerial ownership, leverage and board size as representatives of corporate governance. In measuring financial performance indicators of ROA and firm value are used. SEM-PLS multivariate analysis was used as a data analysis technique. affected by leverage, agency costs and return on assets is significantly Leverage and agency costs have a significant effect on return on assets. leverage and board size have a significant effect on agency costs. Leverage and board size were successfully mediated by agency costs in influencing firm value and ROA.